Droner i sivilsamfunnet Aktører, teknologi og etiske utfordringer - Gynnild, Astrid (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2022)
Civil drones are about to become a billion industry in Norway, and they are often touted as Norway´s new oil. But what exactly do we mean by civil drones, and how can we best ensure that they are used responsibly in society? That is the main question to be discussed in this book. Drones in Civil Society elucidates the topic from many different perspectives. Who are the various actors involved, and how do they work together? What are the differences between civil and military uses of drones? How do we differentiate between the hobby pilot and the professional drone operator, and how can students be trained in responsible, experimental investigation of drone technology? And not least: What happens to the privacy protection of the individual citizen in the midst of all this? The escalating pace of development suggests that drones will soon be an integral part of our everyday lives. What are the implications of this new reality on transportation, business, nature, surveillance, privacy, crime, warfare, and communication?